pH modifies the oxidative potential and peroxide content of biomass burning HULIS under dark aging - Li, Chunlin; Fang, Zheng; Czech, Hendryk; Schneider, Eric; Rüger, Christopher P.; Pardo, Michal; Zimmermann, Ralf; Chen, Jianmin; Laskin, Alexandre; Rudich, Yinon (The Science of the total environment, 2022)
Humic-like substances (HULIS) account for a major redox-active fraction of biomass burning organic aerosols (BBOA). During atmospheric transport, fresh acidic BB-HULIS in droplets and humid aerosols are subject to neutralization and pH-modified aging process. In this study, solutions containing HULIS isolated from wood smoldering emissions were first adjusted with NaOH and NH3 to pH values in the range of 3.6–9.0 and then aged under oxic dark conditions. Evolution of HULIS oxidative potential (OP) and total peroxide content (equivalent H2O2 concentration, H2O2eq) were measured together with the changes in solution absorbance and chemical composition. Notable immediate responses such as peroxide generation, HULIS autoxidation, and an increase in OP and light absorption were observed under alkaline conditions. Initial H2O2eq, OP, and absorption increased exponentially with pH, regardless of the alkaline species added. Dark aging further oxidized the HULIS and led to pH-dependent toxic and chemical changes, exhibiting an alkaline-facilitated initial increase followed by a decrease of OP and H2O2eq. Although highly correlated with HULIS OP, the contributions of H2O2eq to OP are minor but increased both with solution pH and dark aging time. Alkalinity-assisted autoxidation of phenolic compounds and quinoids with concomitant formation of H2O2 and other alkalinity-favored peroxide oxidation reactions are proposed here for explaining the observed HULIS OP and chemical changes in the dark. Our findings suggest that alkaline neutralization of fresh BB-HULIS represents a previously overlooked peroxide source and pathway for modifying aerosol redox-activity and composition. Additionally, these findings imply that the lung fluid neutral environment can modify the OP and peroxide content of inhaled BB-HULIS. The results also suggest that common separation protocols of HULIS using base extraction methods should be treated with caution when evaluating and comparing their composition, absorption, and relative toxicity. [Display omitted] •pH plays a crucial role in determining fresh BB-HULIS characters•Light absorption, OP, and peroxide yield of fresh BB-HULIS increase exponentially with solution pH•Increase solution alkalinity promotes BB-HULIS autoxidation and facilitates OP and peroxides changes in dark aging•Alkalinity-assisted autoxidation of BB-HULIS in lung fluid represents potential health hazard